Cost-Effectiveness of Pembrolizumab for the treatment of Non–Small-Cell lung cancer: A systematic review - Zhang, Chuan; Zhang, Jiaxu; Tan, Jing; Tian, Panwen; Li, Weimin (Frontiers in Oncology, 2022)
Abstract Introduction: Pembrolizumab, an immune checkpoint inhibitor for treating non-small cell lung cancer (NSCLC), can be of high financial burden. A number of studies have explored the cost-effectiveness of this expensive agent. We performed a systematic review and pooled analysis to evaluate the quality of existing pharmacoeconomic studies on pembrolizumab strategies for NSCLC treatment and to conclude the cost-effectiveness of such strategies. Methods: English and Chinese databases were searched to collect health economic studies of pembrolizumab therapies (monotherapy or combination with chemotherapy) compared with traditional chemotherapy for the treatment of NSCLC patients. The reporting quality, modeling methods, and incremental analysis results of the included literature were analyzed descriptively. Results: 25 studies, three in Chinese and 22 in English, were selected. The Markov model, partitioned survival model and micro-simulation model were used for decision analysis. All reports satisfy a median of 31 out of 40 items according to a quality checklist for pharmacoeconomic evaluations. A common limitation of modeling methods lies in the extrapolation of survival data, where the choice of parametric distributions was insufficiently justified, and relevant parameter values were scarcely presented. Pembrolizumab is found to be cost-effective in the United States and Switzerland, but not in China, France, the UK, or Singapore. One-way sensitivity from several studies suggests that the cost of pembrolizumab is likely to be a major factor that impacts the cost-effectiveness results. Conclusion: Current cost-effectiveness studies of pembrolizumab for the treatment of NSCLC are of medium quality, and decision-analytic modeling methods are yet to be improved. Cost-effectiveness of pembrolizumab strategies for NSCLC vary in different countries, more attention should be paid to the methodologies of pharmacoeconomic research to produce correct results of cost-effectiveness in different countries. Systematic Review Registration: PROSPERO, identifier CRD42021250480.